The effectiveness of nature-based interventions in combating PTSD: A meta-analysis and systematic review - Genc, Murat; Alkar, Ozden Yalcinkaya (Academic Press Ltd- Elsevier Science Ltd, 2025)
Post-traumatic stress disorder is generally characterized by the totality of problematic behaviours that occur after exposure to one or more events with a traumatic effect. Different treatment techniques have been developed in the field of psychology for a long time for the treatment of this disorder, which creates a significant expenditure burden for the health system. Nature-based interventions, which are a relatively new approach, have recently been more frequently preferred in the treatment of post-traumatic stress disorder. In this systematic review and meta-analysis study, it was aimed to examine the effect of nature-based interventions on post-traumatic stress disorder. Data were searched in Cochrane Library (CENTRAL), Pubmed, Web of Science (WOS), Scopus, CINAHL (EBSCOhost), Proquest databases in English and YOKTEZ database in Turkish. The last scanning process for all databases was performed on March 03, 2024. 13 experimental studies conducted with a total of 1022 people were included in the meta-analysis. Joanna Briggs Institute (JBI) Critical Appraisal Checklist was used to evaluate the risk of bias of the studies and to conduct the quality study. On the other hand, while Standardized mean difference (SMD) was used to determine the effect size of the study, its heterogeneity was evaluated according to the I2 test. Five different methods were used in the process of evaluating publication bias. In addition, moderator analysis and sensitivity analyses were performed. As a result of the analyses, it was found that nature-based interventions moderately and negatively affected posttraumatic stress symptoms (SMD =-0.558; 95 % CI =-0.678 to-0.437; p = 0.000). Considering the heterogeneity value (I2 = 27.469 %), fixed effect model was used to calculate the effect size since it might to be important level. According to the moderator analysis in which the variable of nature-based intervention techniques (Fishing Activities, Hiking Activities, Recreational Activities) was considered, no significant difference was found between nature-based intervention techniques. It was concluded that nature-based interventions provided significant welfare by moderately reducing the symptoms of posttraumatic stress disorder and that it is a reliable treatment technique that can be preferred by clinicians working in this field.
Keywords: Nature-based interventions; Nature-based therapy; Post-traumatic stress disorder; Trauma; Meta-analysis